CHINA DEBT TRAP MODEL TO SRI LANKA THROUGH THE BELT AND ROAD INITIATIVE PROJECT 2010-2017 - Arwin Kurniansyah; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Every country in the world will not be separated from debt. Poor countries, developing countries, and even developed countries must have debt, both debt obtained from international organizations that provide debt lending services such as the IMF (International Monetary Fund) and the World Bank as well as loans from other countries such as China. In this study, the author will discuss China as a country that can lend funds to other countries through projects created by the President of China, Xi Jinping. In writing this research, the author uses a qualitative case study method. This approach focuses on investigating and understanding an incident by collecting information and then processing it into a final result that can later be presented. The result of this study is that the mastery of the Hambantota port is of course very detrimental to Sri Lanka, this is because it can be seen that China will be able to freely place a war fleet in the South Asian region which can later trigger war. The acquisition of Hambantota Port by China has been debated by the international community. Keywords: Debt Trap Model, China, Sri Lanka